Time-frequency moment interdependence of equity, oil, and gold markets during the COVID-19 pandemic - Walid M. A. Ahmed; Mohamed A. E. Sleem (Cogent Economics & Finance, 2022)
Like no other calamitous event in recent memory, the COVID-19 pandemic has plunged the world's financial system into disarray, triggering systemic risk spillovers across markets. In this study, we use 5-minute index futures price data to examine the multiscale interdependence structure of global equity, gold, and oil markets prior to and following the COVID-19 outbreak, in terms of the first four realized moments of their respective return distributions (i.e., mean, variance, skewness, and kurtosis). With respect to the equity-gold nexus, we find that stock (gold) returns and volatility negatively (positively) lead their gold (stock) counterparts at medium- and long-term scales in the pandemic period, while asymmetry risk in stock markets positively leads its counterpart in gold markets at the same scales before and during the early months of the health crisis. Concerning the oil-equity nexus, our results reveal a positive (negative) co-movement between asymmetry risks at short- and medium-term scales in January-April (May-July) 2020, whereas heavy tail risks are positively synchronized at low frequencies in the turbulent period of March-April 2020. Some policy implications are derived from the analysis.
Keywords: C32; C53; G10; 330; Equity markets; gold; crude oil; realized moments; moment linkage; wavelet phase-difference